2017
DOI: 10.1155/2017/8568347
|View full text |Cite
|
Sign up to set email alerts
|

False Positive Findings on I-131 WBS and SPECT/CT in Patients with History of Thyroid Cancer: Case Series

Abstract: Introduction. Although whole body scan (WBS) with I-131 is a highly sensitive tool for detecting normal thyroid tissue and metastasis of differentiated thyroid cancer (DTC), it is not specific. Additional information, provided by single photon emission computed tomography combined with X-ray computed tomography (SPECT/CT) and by the serum thyroglobulin level, is extremely useful for the interpretation of findings. Case Presentation. We report four cases of false positive WBS in patients with DTC: ovarian uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…An increase in blood flow to the inguinal endometriosis or presence of inflammation in this area might be the reasons for increased radioiodine uptake. Hyperemia, vasodilation, local edema, and increased capillary permeability may cause increased radioiodine uptake in inflamed areas (7,8). In our case, there were multiple reactive lymph nodes around the inguinal mass.…”
Section: öZmentioning
confidence: 53%
“…An increase in blood flow to the inguinal endometriosis or presence of inflammation in this area might be the reasons for increased radioiodine uptake. Hyperemia, vasodilation, local edema, and increased capillary permeability may cause increased radioiodine uptake in inflamed areas (7,8). In our case, there were multiple reactive lymph nodes around the inguinal mass.…”
Section: öZmentioning
confidence: 53%
“…Overall, the literature showed 145 case reports and two series regarding false-positive 131 uptake after RIT For the reasons stated above, we excluded 129 papers, considering only those in which SPECT/CT was performed. A total of 18 papers were thus included: 1 series [17] and 17 case reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The series reported 23 cases of falsepositive results: 15 in the chest, six in the pelvis, one in the cranium, and one in the abdomen.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 20 cases regarded radioiodine uptake in the chest: 11 in the lung (mainly inflammatory), four on the chest bones or on soft tissue due to inflammation/trauma, one in the thymus, one mesenchymal tumor and the rest in not well-characterized sites [17][18][19][20][21]34]. A total of 15 cases regarded uptake in the abdomen/pelvis: six in the kidney (cysts), five in the ovary (teratoma, benign cysts and malignant disease), two in the uterus and the others in not well-characterized sites [22][23][24][25][26][27][28][29]. Three cases reported uptake in the head: two surgical clips, and one on one eye [30,31,33].…”
Section: Resultsmentioning
confidence: 99%
“…Lungo M et al [ 5 ] and Hannoush et al [ 6 ] in 2000 and 2017 reported a false-positive radioiodine uptake in endometrial cyst. Benign cystadenofibroma was reported by Flug J et al [ 7 ].…”
Section: Discussionmentioning
confidence: 99%